KAJIAN TERMINOLOGI BOTANI DAN EKOLOGI TERHADAP ISTILAH TUMBUHAN, TANAMAN, VEGETASI, FLORA, DAN TEGAKAN - Queen Athalia Deborah Rante; Irwanto Irwanto (PT. BARRINGTONIA ASIATICA LESTARI, 2025)
In biological and ecological sciences, the terms tumbuhan (plant/organism), tanaman (cultivated plant), vegetasi (vegetation), flora, and tegakan (stand) are often used interchangeably in everyday discourse. However, these five terms carry distinct definitions, scopes, and conceptual contexts. This article aims to examine and clarify the differences among these terms through terminological, ecological, and biogeographical approaches. Through a literature review of prominent botanical and ecological sources, the study concludes that: (1) tumbuhan refers to individual autotrophic, chlorophyll-bearing organisms as biological entities within taxonomic classification; (2) tanaman refers to plants cultivated by humans for specific purposes and benefits; (3) vegetasi denotes the collective community of plants covering a given area from an ecological perspective; (4) flora refers to the totality of plant species present in a specific geographical region within a biogeographical framework; and (5) tegakan refers to a group of trees or woody plants growing together in a defined area with relative uniformity in composition, structure, and growth conditions. A precise understanding of these five terms is essential for researchers, students, and practitioners in the fields of biology, ecology, forestry, agriculture, and nature conservation.